Sanksi Tindak Pidana Terhadap Pelaku Pencemaran Nama Baik Terhadap Ikatan Dokter Indonesia - Ni Putu Yuni Suantika Putri; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi (Fakultas Hukum Universitas Warmadewa, 2022)
Indonesia is a country consisting of sharing tribes, races, and cultures where each community has their own thoughts and understanding to live their lives. In carrying out his life society is no stranger to the name of human rights where human behavior should not interfere with the rights of others and not behave outside the prevailing norms in accordance with positive laws. In relation to the positive law that applies in Indonesia, the behavior of the community itself has indirectly been regulated and for anyone who behaves outside the norm will definitely get sanctioned because his actions have harmed themselves and others. In accordance with the positive law that applies the act of defamatory has sanctions and fines for anyone who violates it. In the case of Jerinx who said things that satirize certain parties is an act of defamation and in 2020 Jerinx's actions received various responses from the community . Indeed, the goal is to fight for people's rights but does not have to uge out a person's good name and impressed to seek fame in the midst of the Covid-19 outbreak.